Age dependence of the rapid antidepressant and synaptic effects of acute NMDA receptor blockade - Nosyreva, Elena; Autry, Anita E.; Kavalali, Ege T.; Monteggia, Lisa M. (Frontiers in Molecular Neuroscience, 2014)
Ketamine is a NMDA receptor antagonist that produces rapid antidepressant responses in individuals with major depressive disorder. The antidepressant action of ketamine has been linked to blocking NMDA receptor activation at rest, which inhibits eukaryotic elongation factor2 kinase leading to desuppression of protein synthesis and synaptic potentiation in the CA1 region of the hippocampus. Here, we investigated ketamine mediated antidepressant response and the resulting synaptic potentiation in juvenile animals. We found that ketamine did not produce an antidepressant response in juvenile animals in the novelty suppressed feeding or the forced swim test. In addition ketamine application failed to trigger synaptic potentiation in hippocampal slices obtained from juvenile animals, unlike its action in slices from older animals (6-9 weeks old). The inability of ketamine to trigger an antidepressant response or subsequent synaptic plasticity processes suggests a developmental component to ketamine mediated antidepressant efficacy. We also show that the NMDAR antagonist AP5 triggers synaptic potentiation in mature hippocampus similar to the action of ketamine, demonstrating that global competitive blockade of NMDA receptors is sufficient to trigger this effect. These findings suggest that global blockade of NMDA receptors in developmentally mature hippocampal synapses are required for the antidepressant efficacy of ketamine.